Hubungan Tingkat Pengetahuan dan Tingkat Kecemasan Menghadapi Masa Menopause - Panjaitan, Tiffara Keavy Sharon; Haro, Masta (Journal of Telenursing (JOTING), 2024)
This research intends to identify the relationship between the level of knowledge and women's anxiety about facing menopause among women in the Seventh-day Adventist Church Salemba, Central Jakarta. The Method that has been used in this is descriptive quantitative, with a correlative approach to analyze the relationship between the level of knowledge and the level of anxiety that has been measured by a knowledge questionnaire and the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. The results of the research showed that there was a relationship between the level of knowledge and the level of anxiety facing the menopause at the Seventh-day Adventist Church Salemba, Central Jakarta. Keywords: Anxiety, Menopause, Knowlege level